A comparison of different bone graft materials in peri-implant guided bone regeneration - Artas, Gokhan; Gul, Mehmet; Acikan, Izzet; Kirtay, Mustafa; Bozoglan, Alihan; Simsek, Sercan; Dundar, Serkan (Sociedade Brasileira de Pesquisa Odontologica, 2018)
The aim of this study was to compare the effects of hydroxyapatite (HA), deproteinized bovine bone (DPB), human-derived allogenic bone (HALG), and calcium sulfate (CAP) graft biomaterials used with titanium barriers for bone augmentation to treat peri-implant defects in rat calvarium treated by guided bone regeneration (GBR). Thirty-two female Sprague-Dawley rats were divided into four groups: DPB, HALG, HA, and CAP. One titanium barrier was fixed to each rat's calvarium after the titanium implants had been fixed. In total, 32 titanium implants and barriers were used. Ninety days after the surgical procedure, all the barriers were removed. After decalcification of bone tissue, the titanium implants were removed gently, and new bone regeneration in the peri-implant area was analyzed histologically. Immunohistochemical staining of vascular endothelial growth factor (VEGF) was also performed. There were no statistically significant between-group differences in new bone regeneration or VEGF expression after 3 months. According to the results of the histological and immunohistochemical analyses, none of the grafts used in this study showed superiority with respect to new bone formation.
Keywords: Bone Regeneration; Durapatite; Hydroxyapatites; Calcium Sulfate